y=x^{2}-2x-1 \to x=\frac{-b}{2a} = \frac{2}{2 \cdot 1}=1 |
y=3x^{2}-12x+13 \to x=... |
y=-3x^{2}-12x-12 \to x=... |
y=3x^{2}+18x+27 \to x=... |
y=x^{2}-4x+2 \to x=... |
y=x^{2}-2x-1 \to x=... |
y=-2x^{2}+12x-18 \to x=... |
y=-3x^{2}+6x-5 \to x=... |
y=x^{2}+4x+5 \to x=... |
y=x^{2}+2x-1 \to x=... |
y=-2x^{2}+2 \to x=... |
y=2x^{2}+1 \to x=... |
y=-x^{2}+4x-5 \to x=... |
y=2x^{2}-2 \to x=... |
y=-2x^{2}+4x-1 \to x=... |
y=x^{2}-4x+3 \to x=... |
y=-3x^{2}+18x-26 \to x=... |
y=x^{2}-4x+6 \to x=... |
y=-2x^{2}+12x-19 \to x=... |
y=2x^{2}+12x+20 \to x=... |
y=-3x^{2}-12x-14 \to x=... |
y=3x^{2}+12x+11 \to x=... |
y=3x^{2}-18x+26 \to x=... |
y=2x^{2}+2 \to x=... |